The Use of Aizuchi Non Linguistics Form on Keiji Mita's Anime Kimi No Suizou Wo Tabetai - Firmansyah, Akbar Ridho; Khasanah, Umul (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2024)
Anime contains (Japanese) language with various variations including aizuchi. Aizuchi is a response to the speaker as a sign of listening to the speaker's speech. This journal aims to describe the use of sonota or non-linguistik forms of aizuchi sonota and the function of aizuchi in the anime kimi no suizou wo tabetai by Keiji Mita. This research uses pragmatics approach and qualitative descriptive method. The data is in the form of audio visual (video) obtained by observation method, note-taking method and screenshoots to be used as still images. The data of 14 aizuchi in sonota form were analyzed, resulting in the use of 3 aizuchi as kiite iru to iu shingou, 1 aizuchi as rikaishite iru to iu shingou, 1 aizuchi as doi no shingou, 3 aizuchi as hitei no shingou, 5 aizuchi as kanjou no shingou, 1 aizuchi as ma wo motaseru shingou, and 0 aizuchi as jouhou wo tsuika, tessei, youkyu no shingou.